Strategi Pembinaan dan Pemberdayaan Masyarakat dalam Pemanfaatan Hutan Kemasyarakatan - Silya Putri Pratiwi; Dian Kagungan; Eko Budi Sulistio (Jurnal Administrativa, 2020)
Forest management in terms of its production function is directed towards management that is oriented towards all potential forestry resources and is based on community empowerment. The Wana Tekat Mandiri Farmer Group Association manages community forests, namely state forests whose main use is aimed at empowering the community. The rampant illegal logging is carried out by irresponsible parties outside of the farmer group association. So that community groups that carry out illegal logging do not support the Regional Government in providing guidance to the Association of Farmer groups in the Sendang Agung District area. The type of research used in this research is descriptive type with a qualitative approach, data collection techniques, observation, interviews, documentation. The results of this study indicate that the strategy of community development and empowerment in community forest utilization has been running well and the implementation of the strategy has been deemed successful in implementation. The coaching strategy has a main objective in the framework of developing a coaching plan in carrying out activities or programs of Gapoktan Wana Tekad Mandiri, namely by how to develop skills, develop knowledge and develop attitudes. The existence of this coaching strategy is expected to have a good empowering impact on the community.